Pathogenesis and therapy of radiation enteritis with gut microbiota - Yang, Qilin; Qin, Bingzhi; Hou, Weiliang; Qin, Huanlong; Yin, Fang (Frontiers in Pharmacology, 2023)
Radiotherapy is widely used in clinic due to its good effect for cancer treatment. But radiotherapy of malignant tumors in the abdomen and pelvis is easy to cause radiation enteritis complications. Gastrointestinal tract contains numerous microbes, most of which are mutualistic relationship with the host. Abdominal radiation results in gut microbiota dysbiosis. Microbial therapy can directly target gut microbiota to reverse microbiota dysbiosis, hence relieving intestinal inflammation. In this review, we mainly summarized pathogenesis and novel therapy of the radiation-induced intestinal injury with gut microbiota dysbiosis and envision the opportunities and challenges of radiation enteritis therapy.